Improving the knowledge and skills of hemodialysis nurses about intradialytic exercise at Arifin Achmad Hospital, Riau - Erni Forwaty; Usraleli Usraleli; Nia Khusniyati (Community Empowerment, 2022)
The low quality of life of hemodialysis (HD) patients at the Riau Province referral hospital, Arifin Achmad Hospital, is due to dialysis adequacy and low activity levels of hemodialysis (HD) patients. Intradialytic exercise has been shown to improve dialysis adequacy and, as a result, patient quality of life. The aim of this community service is to improve HD nurses' intradialytic exercise knowledge and skills. Training HD nurses on intradialytic exercise is the method of performing community service activities, with implementation approaches including sharing material and skill simulation. The result is that HD nurses have more knowledge and abilities concerning intradialytic exercise, with an average score of 94.3 percent on the post-test. Furthermore, nurses are able to share intradialytic exercise knowledge and skills with HD patients, therefore it is believed that HD patients will be able to use intradialytic exercise to improve their quality of life.